2012
DOI: 10.1007/s00705-012-1450-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype composition of populations of grapefruit-cross-protecting citrus tristeza virus strain GFMS12 in different host plants and aphid-transmitted sub-isolates

Abstract: Citrus tristeza virus (CTV) causes severe losses in grapefruit production in South Africa and requires mild strain cross-protection to maintain production. Unfortunately cross-protection breakdown of the preimmunizing CTV grapefruit mild source GFMS12 is prevalent in grapefruit in South Africa. The CTV genotype composition of the GFMS12 population inoculated onto different hosts was determined by sequencing part of ORF1a and the p23 gene of multiple clones from each plant. Analysis of the GFMS12 population in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 16 publications
4
27
0
1
Order By: Relevance
“…The observed population structure for the sub-isolates tested partially supports and expands upon the results of a previous study [7] in which, based on sequencing multiple clones of amplicons of a segment of ORF1a (A-fragment) and the p23 gene, sub-isolate 12-7 was described as containing an B165/VT-recombinant and an RB/VT-like recombinant, 12-8 a B165/VT-like recombinant, and 12-9 a B165/VT-like recombinant and VT. It is most likely that the B165/VT-like recombinant proposed [7] within all three sub-isolates is actually CT-ZA3, which, like its most closely related isolate T68-1, has been shown by recombination analysis in this study (data not shown) and elsewhere [11] to share most of its 3 0 half with VT, while its ORF1a A-fragment region would have been interpreted in the previous study [7] as a B165-like genotype member in the absence of the subsequently proposed T68 genotype [11].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The observed population structure for the sub-isolates tested partially supports and expands upon the results of a previous study [7] in which, based on sequencing multiple clones of amplicons of a segment of ORF1a (A-fragment) and the p23 gene, sub-isolate 12-7 was described as containing an B165/VT-recombinant and an RB/VT-like recombinant, 12-8 a B165/VT-like recombinant, and 12-9 a B165/VT-like recombinant and VT. It is most likely that the B165/VT-like recombinant proposed [7] within all three sub-isolates is actually CT-ZA3, which, like its most closely related isolate T68-1, has been shown by recombination analysis in this study (data not shown) and elsewhere [11] to share most of its 3 0 half with VT, while its ORF1a A-fragment region would have been interpreted in the previous study [7] as a B165-like genotype member in the absence of the subsequently proposed T68 genotype [11].…”
supporting
confidence: 87%
“…It is most likely that the B165/VT-like recombinant proposed [7] within all three sub-isolates is actually CT-ZA3, which, like its most closely related isolate T68-1, has been shown by recombination analysis in this study (data not shown) and elsewhere [11] to share most of its 3 0 half with VT, while its ORF1a A-fragment region would have been interpreted in the previous study [7] as a B165-like genotype member in the absence of the subsequently proposed T68 genotype [11]. The reported presence of a RB/VT-like recombinant (ORF1a/p23 gene) in sub-isolate 12-7 in addition to B165/ VT [7] is not supported in the current study. In this study, a number of reads from 12-7 mapped to large portions of the 5 0 half of Taiwan-PUM/SP/T1 (also an RB-like genotype) with at least one genome region in this half having high read coverage (c3450), along with some reads in its 3 0 half.…”
mentioning
confidence: 99%
“…The GFMS 35 source was approved as the replacing cross-protecting source for red grapefruit cultivars (Luttig et al 2002) and has been used to pre-immunise red grapefruit budwood mother trees since 1998 (van Vuuren, personal communication).Various molecular techniques have been used to characterise cross-protecting sources and sub-isolates used within the SACIS, which include single stranded conformation polymorphism (SSCP) (Luttig et al 2002) and restriction fragment length polymorphism (RFLP) . Scott et al (2012) used gene amplification and mass cloning to determine the genotype composition of the original GFMS 12 source maintained under glasshouse conditions. Very little data is available regarding the genotype compositions of CTV populations within trees under field conditions.…”
Section: The South African Citrus Improvement Scheme (Sacis) Was Estamentioning
confidence: 99%
“…Folimonova et al (2010) showed that strains provide an absolute exclusion against secondary introductions of the same strain. In light of this, it has been suggested that mild-strains of each strain, present in a region, will need to be obtained and used as cross-protecting sources, in order to elicit effective protection again severe strains present in the field (Scott et al 2012). The process of selecting effective cross-protecting sources is complicated by factors that can influence CTV populations, such as climate (Broadbent et al 1996), varying replicative capacities of strains in different hosts (Targon et al 2000) and variable transmission of certain strains depending on the regional vector population (Roy and Brlansky 2009).…”
Section: Determination Of Primer Bias In the A-region And P23 Genementioning
confidence: 99%
See 1 more Smart Citation